Resveratrol Specifically Kills Cancer Cells by a Devastating Increase in the Ca2+ Coupling between the Greatly Tethered Endoplasmic Reticulum and Mitochondria - Corina T. Madreiter-Sokolowski (2018)
© 2016 The Author(s) Published by S. Karger AG, Basel. Copyright: All rights reserved. Background/Aims: Resveratrol and its derivate piceatannol are known to induce cancer cell-specific cell death. While multiple mechanisms of actions have been described including the inhibition of ATP synthase, changes in mitochondrial membrane potential and ROS levels, the exact mechanisms of cancer specificity of these polyphenols remain unclear. This paper is designed to reveal the molecular basis of the cancer-specific initiation of cell death by resveratrol and piceatannol. Methods: The two cancer cell lines EA.hy926 and HeLa, and somatic short-term cultured HUVEC were used. Cell viability and caspase 3/7 activity were tested. Mitochondrial, cytosolic and endoplasmic reticulum Ca2+ as well as cytosolic and mitochondrial ATP levels were measured using single cell fluorescence microscopy and respective genetically-encoded sensors. Mitochondria-ER junctions were analyzed applying super-resolution SIM and ImageJ-based image analysis. Results: Resveratrol and piceatannol selectively trigger death in cancer but not somatic cells. Hence, these polyphenols strongly enhanced mitochondrial Ca2+ uptake in cancer exclusively. Resveratrol and piceatannol predominantly affect mitochondrial but not cytosolic ATP content that yields in a reduced SERCA activity. Decreased SERCA activity and the strongly enriched tethering of the ER and mitochondria in cancer cells result in an enhanced MCU/Letm1-dependent mitochondrial Ca2+ uptake upon intracellular Ca2+ release exclusively in cancer cells. Accordingly, resveratrol/piceatannol-induced cancer cell death could be prevented by siRNA-mediated knock-down of MCU and Letm1. Conclusions: Because their greatly enriched ER-mitochondria tethering, cancer cells are highly susceptible for resveratrol/piceatannol-induced reduction of SERCA activity to yield mitochondrial Ca2+ overload and subsequent cancer cell death.